A Touch of Genius The Life, Work and Influence of Sir Edward Evans-Pritchard - Singer, Andre (The RAI Series, 2023)
Evans-Pritchard was perhaps the most influential anthropological scholar of the twentieth century. His extraordinary work in Africa has formed a central foundation to anthropological thought since the 1930s, with generations of anthropologists having read and appreciated his ethnographies of the Azande, Nuer and Sanusi, and his analyses of social structures, belief systems and history. And yet, though so much has been written about his work, a rounded understanding of the person has proved elusive. This volume covers Evans-Pritchard as a promising student, a young graduate in search of career opportunities, an adventurous cultural explorer, a determined officer in the Second World War, and an ambitious department-building professor with a global reputation. Against a glittering array of contexts and characters - from Malinowski to Marett to the Maharaj of Kutch; from Oxford poets and pubs to Catholic conversion in war-torn Libya - there emerges a fascinating study of a figure who was much more than an innovative anthropologist. A portrait of the man and his time is composed from personal correspondence, archives and familial recollections, contributions from surviving friends and students, and accounts by those, including contemporary African scholars, who continue to debate and re-evaluate his work in all its complexity. This book is a fitting monument to Evans-Pritchard's legacy and a landmark in anthropological historiography.